Kuroneko - Hayashi, Hikaru 1931-2012 (Eureka Entertainment, 2015)
"In this magnificently eerie and romantic film - loosely based on the Japanese folktale The Cat's Return - a mother and daughter-in-law are raped and murdered by pillagers, but return from the dead as vampiric cat spirits intent on revenge. As the ghosts lure soldiers into the bamboo groves, a fearless samurai, Gintoki, is sent to stop their reign of terror. Kuroneko remains a standout film of the kaidan eiga genre of period ghost stories often based on old legends or kabuki plays. Marking Shindo's first use of wire work as Yone and Shige battle against samurai blades, the film is subtly complimented by Kiyomi Kuroda's award-winning chiaroscuro cinematography, Hikaru Hayashi's vibrant score, and riveting performances from many of the greatest actors of Japan's golden age of film." [amazon.de]
Original: Japan 1968
Bildformat 2.35:1
Gorgeous 1080p HD transfer on the Blu-ray ; optional english subtitles ; original theatrical trailer ; 32-page booklet with an essay by Doug Cummings; a 1972 interview with Shindō conducted by Joan Mellen; and rare imagery
Keywords: Film; DVD-Video; Blu-Ray-Disc